Partial range of motion resistance training: A feasible bodybuilding training regiment for local or regional muscle hypertrophy? - Newmire, D. E.; Willoughby, D. S. (Strength and Conditioning Journal, 2020)
Bodybuilding is defined as an active lifestyle and competitive interest in body aesthetics and muscularity acquired through resistance training. The overall goal in these cosmetically assessed competitions is to display the human physique in a muscularly proportionate and symmetrical manner. Bodybuilding training falls within the hypertrophic oriented goals and recommendations. However, a resistance training modality known as optimal muscle length-specificity training or partial range of motion (pROM) has been recently investigated and has shown some similar hypertrophic outcomes compared to the standard full range of motion (fROM) resistance training. Additionally, there is some work suggesting pROM may have some benefit in local or regional muscular hypertrophy, which may benefit bodybuilding competitors allowing a muscle group focused stimulus. This may be beneficial for competitors who desire to give more attention to underdeveloped muscle groups to create better proportion and symmetry. There are positive yet not definitive results from investigations of pROM on hypertrophy. More research is needed to assess the validity of this mode of training within this population. Bodybuilding is a competition that judges a physique based on proportionate and symmetrical muscularity. The resistance training modality pROM may have benefits for this population.